2019
DOI: 10.1002/gps.5202
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and loneliness among adults aged 50 years or older in six low‐ and middle‐income countries

Abstract: Introduction Loneliness is widespread and associated with deleterious outcomes in middle‐aged and older age people in low‐ and middle‐income countries (LMICs). Physical activity is one potential psychosocial strategy with the potential to reduce loneliness in this population. Thus, the aim of this study was to explore associations between physical activity (PA) and loneliness in middle‐aged and older people from six LMICs. Materials and methods Data from the Study on Global Ageing and Adult Health (SAGE) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 56 publications
3
21
1
5
Order By: Relevance
“…Our findings are aligned with previous research that has linked social support with increased physical activity, 36 and loneliness with physical inactivity. 37 However, one study only identified greater social isolation to be cross-sectionally associated with reduced daily physical activity and sedentary behaviour among 267 participants aged 50-81 years. 38 Notably, daily physical activity was an objective measure in that study, 38 -1801…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are aligned with previous research that has linked social support with increased physical activity, 36 and loneliness with physical inactivity. 37 However, one study only identified greater social isolation to be cross-sectionally associated with reduced daily physical activity and sedentary behaviour among 267 participants aged 50-81 years. 38 Notably, daily physical activity was an objective measure in that study, 38 -1801…”
Section: Discussionmentioning
confidence: 99%
“…compared to our subjective assessment of physical activity.One study conducted in six low-and middle-income countries, links loneliness with physical inactivity among 34,129 adults aged ≥50 years, demonstrating an overall association between loneliness and physical inactivity 37. Social isolation and cardiovascular disease risk factors in the study cohort = and N = 5366 for women and men respectively for all CVD factors, excluding physical activity, where N = 6043 and N = 5297 for women and men respectively.Abbreviations: BMI, body mass index; CVD, cardiovascular disease; HDL, high-density lipoprotein; LDL, low-density lipoprotein.…”
mentioning
confidence: 92%
“…The results of some studies on the associations between RPA and other demographic factors such as age, gender, marital status and income status were inconsistent in different countries [ 41 ]. For example, one study showed no significant association between age and physical activity level [ 20 ], while another study showed that physical activities of older adults had a negative relationship with age [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable logistic regression models were adjusted by age group, education, marital status, subjective socioeconomic status, place of residence, food insecurity, tobacco use status, alcohol use, and body mass index. Confounders were selected based on previous literature review [ 4 , 6 , 11 , 20 ]. P < 0.05 was considered as significant, only complete cases were included, and no multi-collinearity was identified.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding mental health and well-being, studies show that PA reduces fair or poor health [ 2 ], poor mental health [ 1 , 3 ], depression [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], loneliness [ 11 , 12 ], anxiety [ 13 ], and increases life satisfaction and happiness [ 14 ], cognitive function [ 15 , 16 ], and functional ability [ 17 ]. In addition, some studies and a review [ 5 , 18 , 19 , 20 , 21 ] showed that PA or exercise improves sleep quality, including among middle-aged and older adults.…”
Section: Introductionmentioning
confidence: 99%